Behavioural abnormalities in children with new-onset nephrotic syndrome receiving corticosteroid therapy: results of a prospective longitudinal study - Upadhyay, Aishvarya; Mishra, Om P.; Prasad, Rajniti; Upadhyay, Shashi K.; Schaefer, Franz (Pediatric nephrology, 2016)
Corticosteroid therapy can cause behavioural abnormalities in children with nephrotic syndrome. The objective of this study was to explore the timing of the appearance of abnormalities in their first episode.